Mitochondrial catastrophe during doxorubicin‐induced cardiotoxicity: a review of the protective role of melatonin. Issue 4 (18th October 2014) - Govender, Jenelle; Loos, Ben; Marais, Erna; Engelbrecht, Anna‐Mart
Abstract Anthracyclines, such as doxorubicin, are among the most valuable treatments for various cancers, but their clinical use is limited due to detrimental side effects such as cardiotoxicity. Doxorubicin‐induced cardiotoxicity is emerging as a critical issue among cancer survivors and is an area of much significance to the field of cardio‐oncology. Abnormalities in mitochondrial functions such as defects in the respiratory chain, decreased adenosine triphosphate production, mitochondrial DNA damage, modulation of mitochondrial sirtuin activity and free radical formation have all been suggested as the primary causative factors in the pathogenesis of doxorubicin‐induced cardiotoxicity. Melatonin is a potent antioxidant, is nontoxic, and has been shown to influence mitochondrial homeostasis and function. Although a number of studies support the mitochondrial protective role of melatonin, the exact mechanisms by which melatonin confers mitochondrial protection in the context of doxorubicin‐induced cardiotoxicity remain to be elucidated. This review focuses on the role of melatonin on doxorubicin‐induced bioenergetic failure, free radical generation, and cell death. A further aim is to highlight other mitochondrial parameters such as mitophagy, autophagy, mitochondrial fission and fusion, and mitochondrial sirtuin activity, which lack evidence to support the role of melatonin in the context of cardiotoxicity.